2021
DOI: 10.1177/15500594211052815
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging-Guided Transcranial Magnetic and Direct Current Stimulation in MCI: Toward an Individual, Effective and Disease-Modifying Treatment

Abstract: The therapeutic approaches currently applied in Alzheimer's disease (AD) and similar neurodegenerative diseases are essentially based on pharmacological strategies. However, despite intensive research, the effectiveness of these treatments is limited to transient symptomatic effects, and they are still far from exhibiting a true therapeutic effect capable of altering prognosis. The lack of success of such pharmacotherapy-based protocols may be derived from the cases in the majority of trials being too advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Neuroplasticity encompasses various mechanisms, including synaptic plasticity, neurogenesis, and alterations in neuronal connectivity, which underpin crucial processes such as learning, memory, and recovery from injury or disease [ 17 , 18 , 19 , 20 ]. In tandem with understanding neuroplasticity, non-invasive brain stimulation (NIBS) techniques such as transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS) have emerged as promising therapeutic modalities [ 21 , 22 , 23 ]. These techniques can modulate neuroplasticity by inducing changes in cortical excitability and connectivity, offering potential avenues for ameliorating symptoms associated with conditions such as depression, schizophrenia (SCZ), and chronic pain [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neuroplasticity encompasses various mechanisms, including synaptic plasticity, neurogenesis, and alterations in neuronal connectivity, which underpin crucial processes such as learning, memory, and recovery from injury or disease [ 17 , 18 , 19 , 20 ]. In tandem with understanding neuroplasticity, non-invasive brain stimulation (NIBS) techniques such as transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS) have emerged as promising therapeutic modalities [ 21 , 22 , 23 ]. These techniques can modulate neuroplasticity by inducing changes in cortical excitability and connectivity, offering potential avenues for ameliorating symptoms associated with conditions such as depression, schizophrenia (SCZ), and chronic pain [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, pairing a cognitive training intervention with an NIBS technique such as transcranial direct current stimulation (tDCS) has been suggested to be an attractive, safe, and beneficial treatment option [ 4 ]. Combined with training, tDCS increases cortical excitability by changing membrane potentials toward depolarization, tuning ongoing neural processes, and promoting long-term-potentiation-like synaptic plasticity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond immediate effects of the intervention, some studies have observed partially sustained improvements in working memory functions in healthy adults [ 11 13 ]. In patients with cognitive impairment and dementia due to AD, reports of beneficial effects remain limited and heterogeneous [ 4 , 14 , 15 ]. Two randomized controlled trials in patients with early stages of cognitive impairment (such as MCI or mild AD) have reported improved cognitive performance after combined tDCS and training interventions [ 16 , 17 ], while two others did not find intervention benefits [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transcranial magnetic stimulation (TMS), which has long been used successfully in the treatment of depression (Sonmez et al, 2019 ), is now being employed as a possible alternative treatment for other neurodegenerative diseases such as Alzheimer's disease (Freitas et al, 2011 ; Mimura et al, 2021 ), Parkinson's disease, and other dementias (Begemann et al, 2020 ; Hanoglu et al, 2021 ). TMS is a noninvasive approach that uses a magnetic field created outside the body to stimulate or inhibit specific areas of the brain by applying it to the scalp (Hamid et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%